Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1038/onc.2011.243
|View full text |Cite
|
Sign up to set email alerts
|

The effect Akt2 deletion on tumor development in Pten+/− mice

Abstract: The serine/threonine kinase Akt is frequently activated in human cancers and is considered an attractive therapeutic target. However, the relative contributions of the different Akt isoforms to tumorigenesis, and the effect of their deficiencies on cancer development are not well understood. We had previously shown that Akt1 deficiency is sufficient to markedly reduce the incidence of tumors in Pten+/− mice. Particularly, Akt1 deficiency inhibits endometrial carcinoma and prostate neoplasia in Pten+/− mice. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 27 publications
1
27
0
1
Order By: Relevance
“…Previous studies have shown that Akt2 deficiency had little-to-no effect on the tumor spectrum in Pten +/− mice, and only specifically significantly decreased the incidence of thyroid tumors in Pten +/− mice (18), suggesting that AKT2 might play an oncogenic role in thyroid cancer. Recent studies have shown that AKT2 phosphorylates its substrates on both endosomes and the plasma membrane (19).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Previous studies have shown that Akt2 deficiency had little-to-no effect on the tumor spectrum in Pten +/− mice, and only specifically significantly decreased the incidence of thyroid tumors in Pten +/− mice (18), suggesting that AKT2 might play an oncogenic role in thyroid cancer. Recent studies have shown that AKT2 phosphorylates its substrates on both endosomes and the plasma membrane (19).…”
Section: Resultsmentioning
confidence: 92%
“…In the context of breast cancer, AKT2 has been implicated in metastasis, whereas AKT1 suppresses metastatic dissemination (30). Interestingly, signaling through AKT2 is critical for the development of thyroid neoplasms in Pten +/− mice (18). Specifically, loss of Akt2 in Pten +/− mice rescues the development of thyroid adenomas in this model (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The germ line deletion of Akt1 in the mouse does not have adverse physiological consequences, and Akt1 −/− mice live significantly longer than control WT mice (Chen et al, 2006). By contrast germ line deletion of Akt2 induces insulin resistance and does not inhibit tumor development in mouse models of breast cancer and in Pten+/− mice (Maroulakou et al, 2007; Xu et al, 2012). However, studies using germ line deletions of Akt isoforms cannot determine if Akt is required for tumor progression and do not emulate drug therapy.…”
Section: Introductionmentioning
confidence: 96%
“…Similarly, mice lacking Akt1 are protected from tumorigenesis induced by PTEN loss (24). Curiously, a more recent study indicated that inactivation of Akt2 has little or no consequence on prostate neoplasia, explained in part by the relatively little impact of Akt2 loss on total Akt activity and also an increase in blood insulin levels (25). By contrast, Akt2 is required for proliferation and invasive migration of PTEN-deficient glioblastoma (26, 27).…”
Section: Introductionmentioning
confidence: 99%